2019
DOI: 10.1002/slct.201803292
|View full text |Cite
|
Sign up to set email alerts
|

Palladium Acyclic Diaminocarbene (ADC) Triflate Complexes as Effective Precatalysts for the Hiyama Alkynylation/Cyclization Reaction Yielding Benzofuran Compounds: Probing the Influence of the Triflate Co‐Ligand in the One‐Pot Tandem Reaction

Abstract: Palladium acyclic diaminocarbene (ADC) complexes of the type cis-[(R 1 NH)(R 2 )methylidene]Pd(OCOCF 3 ) 2 (CNR 1 ) [R 1 = 2,4,6-(CH 3 ) 3 C 6 H 2 : R 2 = NC 4 H 8 (1); NC 5 H 10 (2)] have been synthesized and structurally characterized. These 1 and 2 complexes are effective precatalysts for the one-pot tandem Hiyama alkynylation/cyclization reaction producing benzofuran compounds and, quite interestingly, higher yields of ca. 33 À 52 % were observed for the aryl triethoxysilylalkyne substrates as compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Using structurally related isocyano Pd(II) diaminocarbene complexes as catalysts, the coupling reactions between triethoxysilylalkynes with iodobenzenes have been recently reported. 86,87 Apart from catalyzing the Sonogashira coupling reactions, some of the isocyano Pd(II) acyclic carbene complexes (Fig. 15(a)) are also active catalysts for the Suzuki cross-coupling reactions.…”
Section: Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using structurally related isocyano Pd(II) diaminocarbene complexes as catalysts, the coupling reactions between triethoxysilylalkynes with iodobenzenes have been recently reported. 86,87 Apart from catalyzing the Sonogashira coupling reactions, some of the isocyano Pd(II) acyclic carbene complexes (Fig. 15(a)) are also active catalysts for the Suzuki cross-coupling reactions.…”
Section: Catalystsmentioning
confidence: 99%
“…Using structurally related isocyano Pd( ii ) diaminocarbene complexes as catalysts, the coupling reactions between triethoxysilylalkynes with iodobenzenes have been recently reported. 86,87…”
Section: Catalystsmentioning
confidence: 99%
“…It was observed that the application of precatalyst 182 exhibited a comparatively higher yield range (15–52%) than precatalyst 181 (10–49%). The essential parameters for the smooth functioning of the corresponding reaction comprised 2 mol% precatalysts 181 and 182 , NaOH in a 4:2 mixture of 1,4-dioxane:H 2 O at 80 °C for 4 h. Maximum yields of 49% and 52% were obtained in case of coupling of 177 with 178 catalyzed by palladium acyclic diaminocarbene (ADC) complexes 181 and 182 precatalysts, respectively ( Figure 6 ) [ 221 ].…”
Section: Applications Of Hiyama Coupling Reactions For the Synthesis ...mentioning
confidence: 99%
“…The easily homemade [Pd(NH 3 ) 4 ]/NaY catalyst appeared to be the best choice for both indoles and benzofurans syntheses, even in reactions where the original Larock procedure failed and for which previous successes required the use of expensive ligand systems [151] (Scheme 48). Recently, Ghosh's group described a convenient one-pot tandem procedure, a Hiyama alkynylation/cyclization reaction of 2-iodophenol with a range of triethoxysilylalkyne compounds in the presence of palladium acyclic diaminocarbene triflate complexes, which produced 2-substituted benzofurans [152]. A novel approach was developed for the synthesis of 2-substituted-3-functionalized benzofurans, in which the first step was the conjugate addition of phenol to an ynone in the presence of a base (K 3 PO 4 gave the highest yield).…”
Section: From O-halophenols and Internal Alkynesmentioning
confidence: 99%